(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper presents Methodology based on super capacitors and battery power management for applications of the ECCE Hybrid Vehicle using the principle of multi boost and full bridge rectifiers. In collaboration with the Electrical and Electronics Research center in Belfort (CREEBEL) and French innovators ECCE for Hybrid vehicle system was developed as an experiment at L2ES Laboratory. An experiment ECCE for the Hybrid Vehicle incorporates the dc motors coupled with the alternator with the rated voltage of 540V. Energy source to the system is by using two super capacitors bank, each bank consists of the 108 cells with provision of maximum voltage of 270V.To embarked the best power management topology for the Hybrid vehicle application, author proposed the multi boost and full bridge converter topologies for it. In this paper the two converter topologies are presented with experimental and the simulation results